Barriers and facilitators to infection prevention and control in a neonatal unit in Zimbabwe – a theory-driven qualitative study to inform design of a behaviour change intervention. Issue 4 (December 2020) - Herbeć, A.; Chimhini, G.; Rosenberg-Pacareu, J.; Sithole, K.; Rickli, F.; Chimhuya, S.; Manyau, S.; Walker, A.S.; Klein, N.; Lorencatto, F.; Fitzgerald, F.C.
Summary: Background: Hospital-acquired infection (HAI) is an increasing cause of neonatal morbidity/mortality in low-income settings. Hospital staff behaviours (e.g., hand hygiene) are key contributors to HAI. Understanding the drivers of these can inform interventions to improve infection prevention and control (IPC). Aim: To explore barriers/facilitators to IPC in a neonatal unit in Harare, Zimbabwe. Methods: Interviews were conducted with 15 staff members of neonatal and maternity units alongside ethnographic observations. The interview guide and data analysis were informed by the COM-B (Capability, Opportunity, Motivation-Behaviour) model and explored individual, socio-cultural, and organizational barriers/facilitators to IPC. Potential interventions were identified using the Behaviour-Change Wheel. Findings: Enablers within Capability included awareness of IPC, and within Motivation beliefs that IPC was crucial to one's role, and concerns about consequences of poor IPC. Staff were optimistic that IPC could improve, contingent upon resource availability (Opportunity). Barriers included: limited knowledge of guidelines, no formal feedback on performance (Capability), lack of resources (Opportunity), often leading to improvization and poor habit formation. Further barriers included the unit's hierarchy, e.g., low engagement of cleaners and mothers in IPC, and staff witnessing implementation of poor practices by other team members (Opportunity). Potential interventions could include role-modelling, engaging mothers and staff across cadres, audit and feedback and flexible protocols (adaptable to water/handrub availability). Conclusions: Most barriers to IPC fell within Opportunity, whilst most enablers fell under Capability and Motivation. Theory-based investigation provides the basis for systematically identifying and developing interventions to address barriers and enablers to IPC in low-income settings.